Profitability of Dry Season Farming of Jute Mallow (Corchorus olitorius) and Amaranth (Amaranthus cruentus) Inter and Sole Cropping Systems in Abeokuta, Nigeria. - Ayodeji Omolola Oladoyin; JONATHAN JEREMIAH ATUNGWU; JAMES OLASUPO FADEYI; DENNIS UGOCHUKWU IFEZUE; Harvester Onyibor Okoye; ADEOLA MOYOSOLUWA AKINWALE (Journal of Agricultural Extension, 2021)
The study determined the profitability of three different cropping systems for the period of six weeks in the study area. Results of the gross margin analysis showed that both the intercropping and only sole amaranthus vegetable production were profitable in the study area, yielding a gross margin of Five hundred and Seventy Nine Thousand, Nine Hundred and Sixteen Naira and Sixty Seven Kobo (N579,916.67)/ha with a total revenue of One Million and Six Hundred Thousand Naira (N1,600,000)/ha and having the highest output of 8000kg/ha for the intercropping systems while the sole Amaranthus vegetable production had a gross margin of One hundred and Seventy Nine Thousand, Nine Hundred and Sixteen Naira, Sixty Seven Kobo (N179,916.67)/ha with a total revenue of One Million and Two Hundred Thousand Naira (N1,200,000)/ha and having the highest output of 6000kg/ha.  Also, the intercrop vegetable production had a Benefit Cost Ratio, Rate of Return and Gross Ratio of 1.53, 0.52 and 0.65 respectively while sole amaranthus production had a Benefit Cost Ratio, Rate of Return and Gross Ratio of 1.15, 0.15 and 0.87 respectively. The result indicates that the two vegetable production were profitable in the study area. However, losses were incurred for the sole C. olitorius vegetable production system during the period of the experiment.